(untitled) (LICERE - Revista do Programa de Pós-graduação Interdisciplinar em Estudos do Lazer, 2025)
The objective of this reflection is to share literature that has focused on experiences of the dismantling of public policies with the aim of highlighting under which conditions public policies become more resistant and resilient in the face of extremist governments. This is a reflective study, theoretically supported by references from political science and the field of public policy. Results. Dismantling does not have a similar impact on all actors, policy areas/sectors and audiences. In the case of sports and leisure policy, an active dismantling at the national level is identified, as well as a failed attempt to change the arena. Final considerations. This literature helps us understand the institutional and political arrangements that result in greater robustness in the configuration of public policies and that must be problematized and sought after in the area of ​​sport and leisure.